Are standard genotoxicity tests useful for the safety evaluation of nanomaterials? - Louro, Henriqueta (2014)
Nanomaterials (NMs) are widely used in a diversity of consumer products, despite uncertainties surrounding the potential health risks that they pose to humans and the environment. One of the major concerns is the potential to induce cancer. To analyze in a short term the carcinogenic properties of a compound, genotoxicity assays in mammalian cell lines or animal models are frequently used. In the context of an EU Joint Action, in the present work we have used standard genotoxicity assays (comet, micronucleus and mutation assays) to investigate the effects associated with the exposure to titanium dioxide nanomaterials (TiO2), following standardized dispersion and assay procedures, in three types of human cells and in a mouse model. The results showed slight but significant increases in the frequencies of micronuclei after exposure to some of the NMs, as compared to controls. No clear dose-response relationships could be disclosed. One of the tested TiO2 yielded equivocal results in vitro micronucleus assay and was positive in the comet assay in pulmonary cells. In view of the inconclusive results,it was further analyzed in vivo, using the lacZ transgenic mouse model. It did not induce genotoxic effects in mice, 28 days after injection, despite the accumulation of the NM observed in the mouse liver. Regarding safety assessment, the different genotoxicity observed for closely related NMs, but that differ in some physicochemical characteristics, highlights the importance of investigating the toxic potential of each NM individually, instead of assuming a common mechanism and equal genotoxic effects for a set of similar NMs. The equivocal genotoxicity of the nanosized TiO2 in human cells in vitro was not confirmed in vivo, and therefore the predictive value of these in vitro tests for identifying genotoxic (and potentially carcinogenic) NMs in vivo should be clarified, before extrapolating the conclusions for human health.